Macbeth melodramma in four acts - Verdi, Giuseppe 1813-1901 (Dynamic, 2015)
Production of Macbeth staged at Novara's Teatro Coccia with Dario Argento tackling for the first time the direction of an opera
Interpr.: Giuseppe Altomare [Macbeth]. Giorgio Giuseppini [Banco]. Dimitra Theodossiou [Lady Macbeth]. Valeria Sepe [Lady-in-waiting]. Dario Di Vietri [Macduff]. Ernesto Petti [Malcom]. Radu Pintillie [Doctor]. Piero Ceffa [Assassin]. Orchestra filarmonica del Piemonte. Schola Cantorum San Gregorio Magno. Mauro Rolfi [Choreinstud.]. Giuseppe Sabbatini [Dir.]. Dario Argento [Bühnenregie]. Marco Scalfi [Filmregie]. - Aufn.: Novara, Teatro Carlo Coccia, 4. - 6. Oktober 2013. - Ital. gesungen. - Text des Beih.: ital., engl. - Untertitel: ital., engl., dt., franz., japan.
Keywords: Verdi, Giuseppe / 1813-1901 / Macbeth; Shakespeare, William -- 1564-1616 -- Macbeth; Operas / Film adaptations; Film; DVD-Video